Safety and effectiveness of intensive treatment for complex PTSD delivered via home-based telehealth - Hannelies Bongaerts; Eline M. Voorendonk; Agnes van Minnen; Ad de Jongh (European Journal of Psychotraumatology, 2021)
Background: Home-based psychotherapy delivered via telehealth has not been investigated in the context of intensive trauma-focused treatment for individuals with severe or Complex posttraumatic stress disorder (PTSD). Objective: To examine the feasibility, safety and effectiveness of an intensive treatment programme containing prolonged exposure, EMDR therapy, physical activities and psycho-education, delivered via home-based telehealth. Method: The treatment was carried out within four consecutive days during the outbreak of the COVID-19 pandemic. The sample consisted of six (four female) patients suffering from severe or Complex PTSD resulting from exposure to multiple traumatic events, mostly during early childhood. Four of them fulfilled the diagnostic criteria of complex PTSD. Outcome measures were the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5), the PTSD Checklist for DSM-5 (PCL-5), and the International Trauma Questionnaire (ITQ). Results: CAPS-5 and PCL-5 scores decreased significantly from pre- to post-treatment (Cohen’s ds 1.04 and 0.93), and from post-treatment to follow-up (Cohen’s ds 0.92 and 1.24). Four of the six patients lost their PTSD or Complex PTSD diagnostic status. No patient dropped out, no personal adverse events and no reliable symptom worsening occurred. Conclusions: The results suggest that intensive, trauma-focused treatment of severe or Complex PTSD delivered via home-based telehealth is feasible, safe and effective, and can be a viable alternative to face-to-face delivered intensive trauma-focused treatment.